2022
DOI: 10.3390/scipharm90040072
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Cationic PAMAM-PLGA Nanoparticles by the Nasal Mucosa

Abstract: Nanoparticles provide promising advantages in advanced delivery systems for enhanced drug delivery and targeting. The use of a biodegradable polymer such as PLGA (poly lactic-co-glycolic acid) promotes improved nanoparticle safety and, to some extent, provides the ability to modify nanoparticle surface properties. This study compared the effect of altering the surface charge on the translocation of PLGA nanoparticles across excised nasal mucosal tissues. Nanoparticles (average diameter of 60–100 nm) loaded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the other hand, another recent study compared the permeation of negatively and positively charged NPs through the olfactory mucosa. 101 Albarki et al concluded in better permeation with the negatively charged NPs. 101 They explained such results as their study was performed for one hour, although other studies were conducted for a longer period of time.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, another recent study compared the permeation of negatively and positively charged NPs through the olfactory mucosa. 101 Albarki et al concluded in better permeation with the negatively charged NPs. 101 They explained such results as their study was performed for one hour, although other studies were conducted for a longer period of time.…”
Section: Resultsmentioning
confidence: 98%
“… 101 Albarki et al concluded in better permeation with the negatively charged NPs. 101 They explained such results as their study was performed for one hour, although other studies were conducted for a longer period of time. 101 The work of Albarki et al contradicts Clementino et.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation